Pengaruh Konseling Alat Kontrasepsi Implan Menggunakan Media Flip Chart terhadap Tingkat Kecemasan Calon Akseptor: The Effect of Implantable Contraceptive Counseling Using Flip Chart Media on the Anxiety Level of Prospective Acceptors - Salsabila Nuriliyah Rashel Rashel; Siti Alfiah; Astuti Setiyani (Gema Bidan Indonesia, 2025)
the city of Surabaya in 2022 is the Non-Long Term Contraceptive Method (Non-MKJP) compared to the Long Term Contraceptive Method (MKJP). The low number of acceptors of contraceptive implants is due to the anxiety level of potential acceptors. This research aimed to determine the effect of implant contraceptive counseling using flip charts on the anxiety level of potential acceptors. This research is Pre-Experimental Design research. The sample taken using a purposive sampling technique was 15 respondents. The independent variable was counseling on contraceptive implants using flip chart media while the dependent variable was anxiety of potential acceptors. Data collection used the Hamilton Anxiety Rating Scale (HARS) questionnaire. The Wilcoxon Signed Ranks Test was used to analyze the presence of influence with a significance value of <0.05. The results of the study showed that the anxiety level of prospective acceptors before being given intervention in the form of counseling on contraceptive implants using flip chart media, the majority (73.3%) of respondents had a mild level of anxiety after being given the intervention to almost all (93.3%) of respondents having no anxiety. From the results of the analysis, the result was 0.001, which means <0.05, so it can be concluded that there is an influence of implant contraceptive counseling using flip chart media on the anxiety level of potential acceptors. Based on the description above, it can be concluded that there is an influence of implant contraceptive counseling using flip chart media on the anxiety level of prospective acceptors. Prospective implant acceptors can use flip charts as a useful information medium, increase their insight, and can use other media to overcome anxiety levels.